THE LINGUOPOETICS OF RURAL MEMORY AND MORAL LANDSCAPE IN RUSSIAN PROSE (American Journal of Pedagogical and Educational Research, 2026)
The present article examines rural memory as a linguopoetic and cultural category in Russian prose and argues that the image of the village in Russian literature should be interpreted not merely as a thematic or ethnographic layer, but as a complex semiotic system in which language, moral evaluation, cultural memory, and historical self-consciousness interact. The study is based on a comparative analysis of selected Russian prose texts associated with the late twentieth and early twenty-first centuries, with special attention to works by Valentin Rasputin, Viktor Astafyev, Guzel Yakhina, and Evgeny Vodolazkin, whose narratives reveal different yet interconnected models of representing land, labor, kinship, speech, and loss. Methodologically, the article combines linguostylistic analysis, narratology, semantic field analysis, discourse analysis, and the theory of cultural memory, which makes it possible to examine both lexical and syntactic organization and deeper symbolic mechanisms through which rural space becomes a bearer of ethical and civilizational meaning. The results show that rural memory in Russian prose is constructed through recurrent lexical clusters related to house, earth, water, bread, road, labor, and kinship; through a specific distribution of narrative voices; through temporal structures that connect biography with collective history; and through moral oppositions embedded in everyday speech. The discussion demonstrates that rural discourse in Russian prose remains productive because it condenses key questions of Russian literary anthropology: the relation between man and land, the fragility of communal solidarity, the ethics of memory, and the crisis of modernity. The article concludes that the linguopoetic study of rural memory provides an effective interdisciplinary model for Russian language and literature research, because it reveals how aesthetic form transforms social experience into durable cultural meaning and how linguistic choices shape literary representations of national identity, historical trauma, and moral continuity.